Development of a stratification tool to identify pancreatic intraductal papillary mucinous neoplasms at lowest risk of progression. Issue 7 (19th August 2019) - Overbeek, Kasper A.; Alblas, Maaike; Gausman, Valerie; Kandel, Pujan; Schweber, Adam B.; Brooks, Christian; Van Riet, Priscilla A.; Wallace, Michael B.; Gonda, Tamas A.; Cahen, Djuna L.; Bruno, Marco J.
Summary: Background: Because most pancreatic intraductal papillary mucinous neoplasms (IPMNs) will never become malignant, currently advocated long‐term surveillance is low‐yield for most individuals. Aim: To develop a score chart identifying IPMNs at lowest risk of developing worrisome features or high‐risk stigmata. Methods: We combined prospectively maintained pancreatic cyst surveillance databases of three academic institutions. Patients were included if they had a presumed side‐branch IPMN, without worrisome features or high‐risk stigmata at baseline (as defined by the 2012 international Fukuoka guidelines), and were followed ≥ 12 months. The endpoint was development of one or more worrisome features or high‐risk stigmata during follow‐up. We created a multivariable prediction model using Cox‐proportional logistic regression analysis and performed an internal‐external validation. Results: 875 patients were included. After a mean follow‐up of 50 months (range 12‐157), 116 (13%) patients developed worrisome features or high‐risk stigmata. The final model included cyst size (HR 1.12, 95% CI 1.09‐1.15), cyst multifocality (HR 1.49, 95% CI 1.01‐2.18), ever having smoked (HR 1.40, 95% CI 0.95‐2.04), history of acute pancreatitis (HR 2.07, 95% CI 1.21‐3.55), and history of extrapancreatic malignancy (HR 1.34, 95% CI 0.91‐1.97). After validation, the model had good discriminative ability (C‐statistic 0.72 in the Mayo cohort, 0.71 in the Columbia cohort, 0.64 in the Erasmus cohort). Conclusion: In presumed side branch IPMNs without worrisome features or high‐risk stigmata at baseline, the Dutch‐American Risk stratification Tool (DART‐1) successfully identifies pancreatic lesions at low risk of developing worrisome features or high‐risk stigmata.